Bottom‐up biodiversity effects increase resource subsidy flux between ecosystems - Daniel C. Allen; Caryn C. Vaughn; Jeffrey F. Kelly; Joshua T. Cooper; Michael H. Engel (Ecology, 2012)
Although biodiversity can increase ecosystem productivity and adjacent ecosystems are often linked by resource flows between them, the relationship between biodiversity and resource subsidies is not well understood. Here we test the influence of biodiversity on resource subsidy flux by manipulating freshwater mussel species richness and documenting the effects on a trophic cascade from aquatic to terrestrial ecosystems. In a mesocosm experiment, mussel effects on algae were linked through stable isotope analyses to mussel‐derived nitrogen subsidies, but mussel biodiversity effects on algal accumulation were not significant. In contrast, mussel biodiversity significantly increased aquatic insect emergence rates, because aquatic insects were responding to mussel‐induced changes in algal community structure instead of algal accumulation. In turn, mussel biodiversity also significantly increased terrestrial spider abundance as spiders tracked increases in aquatic insect prey after a reproduction event. In a comparative field study, we found that sites with greater mussel species richness had higher aquatic insect emergence rates. These results show that, because food webs in adjacent ecosystems are often linked, biodiversity effects in one ecosystem can influence adjacent ecosystems as well.